Teacher’s Perceptions of Online Learning Activities During the Covid-19 Pandemic - Kadek Dwiki Perwira Putra; I Gusti Agung Ayu Wulandari (Universitas Pendidikan Ganesha, 2021)
The Covid-19 pandemic has an impact on all activities including learning activities that were initially carried out through direct interaction between teachers and students, becoming online learning activities. Online learning activities, which are new among elementary school teachers, have resulted in differences in teacher perceptions of online learning activities. This study aims to determine the teacher's perspective on planning, implementing and evaluating learning activities in the network (online). This study used a descriptive research design with a sample of 64 people from a total population of 80 teachers. Data collection used non-test methods with instruments in the form of closed questionnaires. Stages of data analysis using percentage and mean (average). The results obtained in planning learning activities in the network (online) amounted to 77.46% with positive criteria, in the implementation of online learning activities, 66.48% were obtained with the less positive category and in the evaluation of learning activities online (online) obtained 73.34% results with positive criteria. So it can be concluded that teachers' perceptions are positive about planning online learning activities, teachers' perceptions are less positive about planning online learning activities, and teachers' perceptions are positive about evaluating online learning activities.